PENGUATAN PEMAHAMAN DAN IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA ROHIS SEKOLAH MENENGAH ATAS - Supani, Supani; Yaqin, Ainul; Erlina, Fatni (Universitas Islam 45 Bekasi, 2025)
The focus of this service is an effort to instill an understanding and attitude of religious moderation in the Rohis organization at the high school level in Banyumas Regency and efforts to implement it in the school and community environment. The method used in this service is the ABCD method. The target of the service is Rohis in high schools in Banyumas Regency, a total of 25 public and private SMA/MA/SMK schools. The results of this service are the activities of planting understanding and attitudes of religious moderation in Rohis organizations at the high school level in Banyumas Regency with the main activities in the form of workshops and mentoring. This assistance is carried out to implement the values of religious moderation by Rohis in the environment of educational institutions and society. The form of assistance is through offline assistance by creating events in collaboration with the service team and online assistance such as discussions via Whatsapp. The impact of the implementation of the values of religious moderation is clearly visible, where the understanding of Rohis members increases and students' attitudes and behaviors experience positive changes. Students began to demonstrate the values of religious moderation, such as tolerance, mutual respect, and openness to differences. Thus, this effort not only strengthens students' character, but also contributes to the creation of a more harmonious environment in schools and communities in Banyumas Regency.